Assessing the Italian innovative start-ups performance with a composite index - Gianni Onesti; Eleonora Monaco; Riccardo Palumbo (Administrative Sciences, 2022)
This paper aims to assess the profitability and employees' productivity of Italian innovative start-ups with a new composite index: the Start-ups Performance score (SP-score). In recent years, the Italian government has made several efforts to foster the economy, establishment, and growth of start-ups. Specifically, the issuing of the Italian Start-up Act in 2012 offers a unique opportunity to examine the Italian setting, given the special conditions that the government granted to the start-ups. The latter obtain generic benefits, tax reductions and hiring facilitations if they meet specific criteria granting the status (label) of 'innovative' by law. Based on a sample of Italian start-ups firms (ISPs) and financial statement data for the period 2016-2020, we test whether the performance of the Italian start-ups which are granted the status of 'innovative' is higher compared to start-ups without the mentioned status (NISPs). We measure the firm's performance by building a composite index which synthesizes both profitability and employees' productivity (controlling for the firms' size), and find that the ISPs report higher SP-score compared to the NISPs. In addition, we examine whether the SP-score is higher (or lower) among Innovative start-ups located in different regional areas. The derivation of the composite indicator (SP-score) allows a clear and effective evaluation of several characteristics, permitting a more comprehensive understanding of the data that support the strategic choices of management and localization entrepreneurship policies. In addition, our study highlights a certain homogeneity of innovative start-ups' performance among the Italian territories, which overcomes the classic dualistic division between Northern and Southern regions.
Keywords: 350; composite indicators; entrepreneurship; financial statement analysis; innovative start-ups; start-ups performance